RehabCity: design and validation of a cognitive assessment and rehabilitation tool through gamified simulations of activities of daily living - Vourvopoulos, Athanasios (2019)
Worldwide, more than one in three adults suffers from a cardiovascular disease. According to the World Health Organization, 15 million people experience a stroke each year and, of these, 5 million stay permanently disabled. The current limitations of traditional rehabilitation methods push towards the design of personalized tools that can be used intensively by patients and therapists in clinical or athome environments. In this paper we present the design, implementation and validation of RehabCity, an online game designed for the rehabilitation of cognitive deficits through a gamified approach on activities of daily living (ADLs). Among other findings, our results show a strong correlation between the RehabCity scoring system and the Mini Mental State Examination test for clinical assessment of cognitive function in several domains. These findings suggest that RehabCity is a valid tool for the quantitative assessment of patients with cognitive deficits derived from a brain lesion.